ChemInform Abstract: Palladium‐Catalyzed Directed para C—H Functionalization of Phenols. Issue 45 (October 2016) - Patra, Tuhin; Bag, Sukdev; Kancherla, Rajesh; Mondal, Anirban; Dey, Aniruddha; Pimparkar, Sandeep; Agasti, Soumitra; Modak, Atanu; Maiti, Debabrata
Abstract: The directing‐group‐assisted para C—H functionalization of toluene derivatives occurs under assistance of a recyclable silicon‐containing biphenyl‐based template.